Speaking Modernity: From the “Debate between Traditional Chinese Medicine and Western Medicine” to the “Debate between Science and Metaphysics”: A Study of Media Discourse Based on the “Proposal of Abolishing Traditional Chinese Medicine” in the Republic of China - WANG, Nan; Xu, Jing (The Journal of Medicine, Humanity and Media, 2024)
Abstract：After the outbreak of COVID-19, the battle between Traditional Chinese Medicine (TCM) and Western Medicine as a disease diagnosis and treatment system has once again become one of the focuses in public opinion. The “debate between TCM and Western Medicine” is not a new debate triggered by the pandemic, but a game between science and metaphysics, modernity and non-modernity already triggered by the collision of Eastern and Western civilizations in modern times. This study takes the “Proposal of Abolishing Traditional Chinese Medicine” in 1929 as a case study, and examines how the medical publications participate in and construct the “debate between TCM and Western Medicine” and the “debate between science and metaphysics” through media discourse, so as to speak modernity. It is found that the media discourse of “abolishing TCM” contains four discourse debate forms: abolishing TCM completely, refusing to abolish TCM, following the Western medicine system to reform TCM, and “Sinicizing” to reform TCM, which has become a typical representation of the “debate between TCM and Western Medicine” and “debate between science and metaphysics”. Furthermore, these media discourses reflect the “Sinicized” modernity construction mode of the Republic of China society, which establishes “the other” to imagine modernity and denies metaphysics and its cultural forms to speak modernity. Keywords：Modernity; the debate between Traditional Chinese Medicine (TCM) and Western medicine; the debate between science and metaphysical; media discourse; the Proposal of Abolishing TCM